2015
DOI: 10.1183/09031936.00141614
|View full text |Cite
|
Sign up to set email alerts
|

Interaction effect of psychological distress and asthma control on productivity loss?

Abstract: Little is known about the potential synergistic effect of comorbid psychological distress (PD) and uncontrolled asthma (UA) on productivity loss. We estimated the productivity loss associated with the combination of these two potentially preventable conditions in employed adults with asthma.A population-based random sample of 300 adults with asthma in British Columbia, Canada, was prospectively recruited between Dec 2010 and Aug 2012. PD and productivity loss due to absenteeism and presenteeism was measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…In that study, work disability was defined as long-term sickness absence (≥90 days) and receiving a disability pension. Results of current study are inline with our previous study that demonstrated the presence of comorbid psychological conditions in asthma patients will increase productivity loss significantly [28]. …”
Section: Discussionsupporting
confidence: 90%
“…In that study, work disability was defined as long-term sickness absence (≥90 days) and receiving a disability pension. Results of current study are inline with our previous study that demonstrated the presence of comorbid psychological conditions in asthma patients will increase productivity loss significantly [28]. …”
Section: Discussionsupporting
confidence: 90%
“…The findings for depression and anxiety are novel, yet are not unexpected, given studies in non‐asthma populations . Effects of depression and anxiety on productivity may be even more profound than asthma control, highlighting the importance of improving mental health in severe asthma. We identified few other predictors of presenteeism among a range of demographic, asthma and health status characteristics.…”
Section: Discussionmentioning
confidence: 94%
“…The findings for depression and anxiety are novel, yet are not unexpected, given studies in nonasthma populations 42,43. Effects of depression and anxiety on productivity may be even more profound than asthma control,44 Associations between asthma severity characteristics, health status characteristics and immunological indicators at baseline. Abbreviations: CI, confidence interval; FEV 1 %, forced expiratory volume in 1 s % predicted (10 unit change); HADS, Hospital Anxiety and Depression Scale: OR, odds ratio highlighting the importance of improving mental health in severe asthma.…”
mentioning
confidence: 92%
“…Ojeda et al estimated that adults had 1.5 missed days per month due to asthma symptoms and 4.9 days per month of reduced productivity [52]. Uncontrolled asthma causes more lost productivity compared to patients with well-controlled symptoms, with a loss of approximately CAD$286 (US$219) per week [50,54]. In Spain, approximately 285 Euros (US$315) were attributed to lost workdays per patient each month [50,52].…”
Section: Cost Of Asthma Carementioning
confidence: 99%